Terahertz sensing with high sensitivity and substance identification capability using a novel High-quality resonance supported by a thin structured silicon film. (August 2022) - Sun, Min; Maqbool, Esha; Han, Zhanghua
Highlights: A new terahertz sensing scheme based on the new physics of bound state in the continuum is proposed. The terahertz sensing only needs an ultrathin structure whose thickness is only 1/3 of the operation wavelength. The detection scheme can provide both a high sensitivity and a substance capability of the terahertz spectroscopy. Abstract: We propose and numerically investigate a novel gas sensing structure with large sensitivity and the capability of substance selectivity, as well as high compactness based on the terahertz spectroscopic technique, by using a novel high-quality resonance, which is designed to match the absorption characteristic frequency of the target chemical. The resonance is achieved by employing the concept of bound state in the continuum (BIC), supported by a simple structure of silicon slab perforated by an interdigitated slot array with alternating slot width. An example of the detection of a toxic gas of HCN (hydrogen cyanide) was demonstrated and it is shown that a HCN concentration as low as 2 ppm in air under the atmospheric pressure of 1 atm can be detected with a slab thickness less than 100 μm. The selectivity of this assembled structure is also confirmed by introducing non-target Hydrogen bromide (HBr) gas, with no transmission drop at the original resonance. It refers to the conclusion that this structure shows great potential for practical applications for both gas identification and concentration monitoring.